2017 IEEE International Conference on Data Mining Workshops (ICDMW) 2017
DOI: 10.1109/icdmw.2017.124
|View full text |Cite
|
Sign up to set email alerts
|

Performance Dynamics and Success in Online Games

Abstract: Abstract-Online data provide a way to monitor how users behave in social systems like social networks and online games, and understand which features turn an ordinary individual into a successful one. Here, we propose to study individual performance and success in Multiplayer Online Battle Arena (MOBA) games. Our purpose is to identify those behaviors and playing styles that are characteristic of players with high skill level and that distinguish them from other players. To this aim, we study Defense of the an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

6
1

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…Then we verified our findings via randomization to exclude the possibility that the performance deterioration phenomenon was created by chance (random effect). The right plot of Figure 3 shows the reshuffled data, where the effect of match position is disrupted: as we would expect, the lines flatten out suggesting that indeed the position of a match in a session has an effect on performance, corroborating the performance deterioration hypothesis in line with recent research results [22], [23], [24].…”
Section: Rq3: Influence Of Social Ties On Individuals Over Sessionssupporting
confidence: 86%
See 1 more Smart Citation
“…Then we verified our findings via randomization to exclude the possibility that the performance deterioration phenomenon was created by chance (random effect). The right plot of Figure 3 shows the reshuffled data, where the effect of match position is disrupted: as we would expect, the lines flatten out suggesting that indeed the position of a match in a session has an effect on performance, corroborating the performance deterioration hypothesis in line with recent research results [22], [23], [24].…”
Section: Rq3: Influence Of Social Ties On Individuals Over Sessionssupporting
confidence: 86%
“…Other than individual online behaviors, short-term deterioration effects has also been found in virtual teams in MOBA games. [22], [23], [24]. These results pose the basis for RQ3 and RQ4: our analysis revealed that social ties can play a role in mitigating performance deterioration over the course of an activity session, however such a mitigation is not homogeneous across all individuals, but tend to benefit more the low-skilled or low-experienced ones, while high-skill or high-experience individuals may not be affected by social ties when it comes to mitigating performance deterioration.…”
Section: Performance Deterioration Dynamicsmentioning
confidence: 99%
“…This genre of games, including Heroes of the Storm, Dota 2, and League of Legends, has attracted researchers from different fields, especially because they provide a unique way to study the influence of role-playing in competitive games [1,2], the impact of cooperation [3,4] versus individual player attitudes [5,6], social behaviors [7][8][9], user commitment [10], etc. The analysis of MOBA games also allows for the discovery of useful information to study the social dynamics of player communities.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research investigated factors influencing human performance in MOBA games. On the one hand, studies focus on identifying player's choices of role, strategies as well as spatio-temporal behaviors (Drachen et al, 2014 ; Yang et al, 2014 ; Eggert et al, 2015 ; Sapienza et al, 2018b ) that drive players to success (Sapienza et al, 2017 ; Fox et al, 2018 ). On the other hand, performance may be affected by player's social interactions: the presence of friends (Pobiedina et al, 2013a ; Park and Kim, 2014 ; Sapienza et al, 2018b ), the frequency of playing with or against certain players (Losup et al, 2014 ), etc.…”
Section: Introductionmentioning
confidence: 99%